Research progress of factors influencing lip morphology and their relevance to orthodontic treatment - XIA Xueyan, WU Mengjie (Editorial Office of Stomatology, 2024)
The lip plays a crucial role in facial aesthetics, making them a focal point of interest for orthodontists and patients throughout orthodontic treatment due to their three-dimensional changes in morphology and position. The degree of improvement in lip morphology significantly impacts post-treatment satisfaction among orthodontic patients. Therefore, understanding the influencing factors of lip morphology and its correlation with orthodontic interventions enables orthodontists to predict post-treatment changes in lip morphology more accurately, facilitating the customization of orthodontic treatment plans. In this paper, we reviewed the progress of methods for evaluating lip morphology and its influencing factors in order to provide reference for clinical practice.